Effects of CNTs content on the microstructure and mechanical properties of spark plasma sintered TiB2-SiC ceramics. Issue 1 (January 2017) - Lin, Jia; Yang, Yihang; Zhang, Houan; Gong, Junfei
Abstract: Monolithic TiB2 ceramics and TiB2 −20 vol%SiC- x vol%CNTs ( x =0, 5, 10, 15, 20, 25 and 30) composites were prepared by spark plasma sintering. The influence of CNTs content and sintering temperature on sintering behavior, microstructure and mechanical properties were investigated. It was indicated that the fine grains, increased densification and homogenous dispersion of CNTs were the main dominate factors for the improved mechanical properties. The highest flexural strength (925±45 MPa) and fracture toughness (10.4±0.3 MPa m 1/2 ) were achieved in composite with 15 vol% CNTs sintered at 1750 °C. The toughness mechanism was ascribed to be crack deflection, crack bridging, CNTs debonding and pull-out. However, porous rope-like structure of agglomerated CNTs was observed by more than 20 vol% CNTs addition, resulting in the reduction of relative density and mechanical properties.